The Implementation of Brain-Writing Strategy to Enhance Hortatory Essay in High School Students’ Writing - Nahdah Mardhiyyatussa‘diyah; Sueb Sueb (Scripta : English Department Journal, 2023)
This research explores the implementation of the brain-writing strategy as an instructional approach to address the writing challenges encountered by students of secondary school level. Writing difficulties often arise due to incomplete involvement in the different stages of the writing process, especially a pre-writing stage. The aim of this study is to overcome the issues by utilizing the brain-writing strategy on the teaching of hortatory writing, while evaluating its impact on both student performance and perception. A triangulation mixed method was employed as the research design, integrating multiple data collection techniques from an observation, tests, and a classroom survey on perception. The study took place in a public high school, with a purposive sampling technique utilized to select 36 eleventh-grade students as participants. This sampling method ensured the deliberate selection of participants based on specific criteria pertinent to the research objectives. The findings that was collected from some observations illuminated the implementation of brain-writing strategy as an instructional strategy to enhance students’ writing skills, especially in the content and structure. Through the analysis of data collected via various methods, the researchers gained insights into the improvements in students’ performance and their perceptions of the strategy. This research contributes to the existing knowledge on effective writing instruction and offers valuable information for educators seeking innovative strategies to enhance students’ hortatory writing abilities. Ultimately, the findings aim to inform educational practices and assist students in overcoming writing challenges.